Analyses of long non-coding RNA and mRNA profiling in the spleen of diarrheic piglets caused by Clostridium perfringens type C - Yan,Zunqiang; Huang,Xiaoyu; Sun,Wenyang; Yang,Qiaoli; Shi,Hairen; Jiang,Tiantuan; Li,Shenggui; Wang,Pengfei; Gun,Shuangbao (PeerJ, 2018)
Background Clostridium perfringens (C. perfringens) type C is the most common bacteria causing piglet diarrheal disease and it greatly affects the economy of the global pig industry. The spleen is an important immune organ in mammals; it plays an irreplaceable role in resisting and eradicating pathogenic microorganisms. Based on different immune capacity in piglets, individuals display the resistance and susceptibility to diarrhea caused by C. perfringens type C. Recently, long non-coding RNA (lncRNA) and mRNA have been found to be involved in host immune and inflammatory responses to pathogenic infections. However, little is known about spleen transcriptome information in piglet diarrhea caused by C. perfringens type C. Methods Hence, we infected 7-day-old piglets with C. perfringens type C to lead to diarrhea. Then, we investigated lncRNA and mRNA expression profiles in spleens of piglets, including control (SC), susceptible (SS), and resistant (SR) groups. Results As a result, 2,056 novel lncRNAs and 2,417 differentially expressed genes were found. These lncRNAs shared the same characteristics of fewer exons and shorter length. Bioinformatics analysis identified that two lncRNAs (ALDBSSCT0000006918 and ALDBSSCT0000007366) may be involved in five immune/inflammation-related pathways (such as Toll-like receptor signaling pathway, MAPK signaling pathway, and Jak-STAT signaling pathway), which were associated with resistance and susceptibility to C. perfringens type C infection. This study contributes to the understanding of potential mechanisms involved in the immune response of piglets infected with C. perfringens type C.
Keywords: Swine; Diarrhea; LncRNA; Clostridium perfringens type C; Spleen